Protocol to estimate the heritability of drug response with GxEMM and identify gene-drug interactions with TxEWAS - Michal Sadowski; Andy W. Dahl; Noah Zaitlen (STAR Protocols)
Summary: Identifying factors that affect treatment response is a central objective of clinical research. Here, we present a protocol to study the genetic architecture of response to commonly prescribed drugs using gene-context interaction techniques. We describe steps for estimating the heritability of drug response with gene-environment interaction mixed model (GxEMM) and identifying gene-drug interactions with gene-environment interaction transcriptome-wide association study (TxEWAS). While the protocol describes application to drug treatments, this framework can be used to characterize the genetic basis of any covariate’s effect.For complete details on the use and execution of this protocol, please refer to Sadowski et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.